2020
DOI: 10.1038/s41419-020-2656-0
|View full text |Cite
|
Sign up to set email alerts
|

SHQ1 is an ER stress response gene that facilitates chemotherapeutics-induced apoptosis via sensitizing ER-stress response

Abstract: SHQ1 was reported to control the biogenesis and assembly of H/ACA ribonucleoprotein particles (RNPs). It was independently isolated as a growth suppressor, GRIM1, in a genetic screen. Recent studies have indicated that SHQ1 inhibits prostate cancer growth and metastasis. SHQ1 facilitates MYC RNA splicing to promote T-acute lymphoblastic leukemia (T-ALL) development. Thus, the mechanisms of SHQ1 in cancers remain largely unknown. We report here that SHQ1 promotes tumor apoptosis and chemo-sensitivity in hepatoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Moreover, our data demonstrated that SHQ1 expression in anlotinib‐resistant A549 cells was also upregulated by β‐sitosterol. SHQ1 is a response gene of ER stress that can induce UPR activation (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, our data demonstrated that SHQ1 expression in anlotinib‐resistant A549 cells was also upregulated by β‐sitosterol. SHQ1 is a response gene of ER stress that can induce UPR activation (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al discovered that the H/ACA ribonucleoprotein assembly factor (SHQ1) is a new ER stress response gene. SHQ1 enhances the sensitivity of hepatocellular carcinoma to chemotherapy by promoting ER stress and activating the UPR (Liu et al, 2020); however, it is unclear whether βsitosterol can sensitize drug-resistant lung cancer cells by attenuating SHQ1.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that chemotherapeutic drugs act via induction of ER stress [ 10 , 11 ]. It is important to note that moderate ER stress can induce cancerous cells' proliferative ability via elevating their capacity for biosynthesis.…”
Section: Introductionmentioning
confidence: 99%